Role of Polyphosphate as an Inorganic Chaperone to Prevent Protein Aggregation Under Copper Stress in Saccharolobus solfataricus - José Acevedo-López; Gabriela González-Madrid; Claudio A. Navarro; Carlos A. Jerez (Microorganisms)
Polyphosphates are biopolymers composed of phosphate monomers linked by high-energy phosphoanhydride bonds. They are present across all life domains, serving as a source of energy, metal chelators, and playing a crucial role in stress defense. In Escherichia coli, polyphosphates also function as inorganic molecular chaperones. The present study aims to investigate whether polyphosphate serves a similar chaperone function in archaea, using Saccharolobus solfataricus as a model organism. To this end, polyphosphate was extracted and quantified, the ADP/ATP ratio was determined, insoluble protein extracts were analyzed at different time points after copper exposure, and qPCR was performed to measure the expression of stress-related genes. PolyP was extracted after exposing the archaeon S. solfataricus to different copper concentrations. We determined that polyP degradation is directly correlated with metal concentration. At the minimum inhibitory concentration (MIC) of 2 mM Cu2+, polyP degradation stabilized 2 h after exposure and showed no recovery even after 24 h. The ADP/ATP ratio was measured and showed differences in the presence or absence of polyP. The analysis of proteins precipitated under copper stress showed a higher proportion of insoluble proteins at an elevated metal concentration. On the other hand, increased protein precipitation was detected in the absence of polyP. Gene expression analysis via qPCR was conducted to assess the expression of genes involved in chaperone and chaperonin production, copper resistance, oxidative stress response, and phosphate metabolism under prolonged copper exposure, both in the presence and absence of polyP. The results indicated an upregulation of all the chaperonins measured in the presence of polyP. Interestingly, just some of these genes were upregulated in polyP’s absence. Despite copper stress, there was no upregulation of superoxide dismutase in our conditions. These results highlight the role of polyP in the copper stress response in S. solfataricus, particularly to prevent protein precipitation, likely due to its function as an inorganic chaperone. Additionally, the observed protein precipitation could be attributable to interactions between copper and some amino acids on the protein structures rather than oxidative stress induced by copper exposure, as previously described in E. coli. Our present findings provide new insights into the protective role of polyP as an inorganic chaperone in S. solfataricus and emphasize its importance in maintaining cellular homeostasis under metal stress conditions.